PENGARUH PERENCANAAN KERJA, MOTIVASI KERJA DAN KOORDINASI KERJA TERHADAP KINERJA PEGAWAI DI KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI - Yulihardi, Yulihardi; Iskamto, Dedi (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
This study aims to analyze, Influence Work Planning, Work Motivation, and Work Coordination either partially or jointly to the Performance of North Sipora Subdistrict, Mentawai Islands District. The main problem in this research is